The Influence of Promotion, Perceived Ease of Use, and Price Toward Repurchase Intention Transportation Services Go-jek on Students in Universitas Negeri Padang - Aulia Restu Yohanda; Erni Masdupi; Yunita Engriani (Jurnal Kajian Manajemen dan Wirausaha, 2019)
Purpose - The purpose of this research to analyze: (1) The influence of Promotion onRepurchase Intention Transportation Services Go-Jek On Students in Padang State University(2) The influence of Perceived Ease of Use on Repurchase Intention Transportation ServicesGo-Jek On Students in Padang State University (3) The influence of Price on RepurchaseIntention Transportation Services Go-Jek On Students In Padang State University.Methodology - This type of research is descriptive research. The population in this study wereall students at Padang State University User Go-Jek transportation services with a total sampleof 170 people taken using convenience sampling because of the unknown population.Finding - Regarding the causal model proposed, the data confirm the relationship set out in thehypothesis. It can therefore be stated that ((1) Promotion significant effect on RepurchaseIntention Transportation Services Go-Jek On Students in Padang State University (2) PerceivedEase Of Use significant effect on Repurchase Intention Transportation Services Go-Jek OnStudents In Padang State University (3) Price Use significant effect on Repurchase IntentionTransportation Services Go-Jek On Students In Padang State University.Limitation - This research only limit with some variablesKeywords: Promotion, Perceived Ease Of Use, Price and Repurchase IntentionLatar Belakang